Safety and immunogenicity of a 13-valent pneumococcal conjugate vaccine in adults 50 to 65 years of age in India: An open-label trial - Solanki, Bhagirath B. (Hum Vaccin Immunother, 2017)
Streptococcus pneumoniae infection is a major global public health concern in older adults, especially as life expectancy continues to increase in most countries, including India. Recently, a 13-valent pneumococcal conjugate vaccine (PCV13) with the ability to enhance immunity (immunologic memory) on natural exposure or revaccination has been shown to protect against community-acquired pneumonia and invasive pneumococcal disease in adults 65 years of age and older. An unconjugated 23-valent pneumococcal polysaccharide vaccine has been available for decades; however, data on protection against pneumonia are inconsistent. For the first time, a multicenter study has been conducted in India to assess the safety and immunogenicity of a single dose of PCV13 in adults aged 50 to 65 years. In this study, PCV13 elicited robust immune responses against all 13 pneumococcal serotypes as reflected by the magnitude of geometric mean fold rises (range, 6.6–102.7) in functional antibody levels from before to 1 month after vaccination. No serious adverse events occurred. These clinical trial findings support the safety and immunogenicity of PCV13 when administered to adults in India and indicate that a single dose of PCV13 has the potential to protect against vaccine-type pneumococcal disease in adults aged 50 to 65 years. ClinicalTrials.gov identifier: NCT02034877